To simplify the expression \( \frac{56r}{4t} + \frac{-12}{4t} \), we can first simplify each term separately.
-
For the first term \( \frac{56r}{4t} \): \[ \frac{56r}{4t} = \frac{56}{4} \cdot \frac{r}{t} = 14 \cdot \frac{r}{t} = \frac{14r}{t} \]
-
For the second term \( \frac{-12}{4t} \): \[ \frac{-12}{4t} = \frac{-12}{4} \cdot \frac{1}{t} = -3 \cdot \frac{1}{t} = \frac{-3}{t} \]
Now we can combine the two terms: \[ \frac{14r}{t} + \frac{-3}{t} = \frac{14r - 3}{t} \]
Thus, the final result of the expression is: \[ \frac{14r - 3}{t} \]
Therefore, the quotient when dividing \( \frac{56r}{4t} + \frac{-12}{4t} \) simplifies to \( \frac{14r - 3}{t} \).